A radical approach to radicals. Issue 1 (23rd December 2021) - Liu, Youjia; Biczysko, Malgorzata; Moriarty, Nigel W.
Abstract : New restraints for the nitroxide radical ligand MTN defined based on quantum‐chemical computations allow the accurate re‐refinement of protein structures. Abstract : Nitroxide radicals are characterized by a long‐lived spin‐unpaired electronic ground state and are strongly sensitive to their chemical surroundings. Combined with electron paramagnetic resonance spectroscopy, these electronic features have led to the widespread application of nitroxide derivatives as spin labels for use in studying protein structure and dynamics. Site‐directed spin labelling requires the incorporation of nitroxides into the protein structure, leading to a new protein–ligand molecular model. However, in protein crystallographic refinement nitroxides are highly unusual molecules with an atypical chemical composition. Because macromolecular crystallography is almost entirely agnostic to chemical radicals, their structural information is generally less accurate or even erroneous. In this work, proteins that contain an example of a radical compound (Chemical Component Dictionary ID MTN) from the nitroxide family were re‐refined by defining its ideal structural parameters based on quantum‐chemical calculations. The refinement results show that this procedure improves the MTN ligand geometries, while at the same time retaining higher agreement with experimental data.